Pengaruh Suplementasi Asam Folat Terhadap Kontrol Glikemik Pada Pasien Diabetes Melitus Tipe 2: Evidence-Based Case Report - Lumbantoruan, Isabella Febrina; Sonia, Steffi (Jurnal sosial dan sains, 2025)
Type 2 Diabetes Mellitus is a chronic non-communicable disease that is projected to continue increasing globally, thereby placing a burden on healthcare systems in both developed and developing countries. High levels of homocysteine have been associated with insulin resistance and may contribute to the development of Type 2 Diabetes Mellitus. The administration of folate, either alone or in combination with other B vitamins, has been proven effective in reducing homocysteine concentrations. Aim: to determine the effectiveness of folate supplementation as an adjuvant therapy for patients with type 2 Diabetes Mellitus in correcting glycemic control, as measured by glucose homeostasis markers. Methods: Literature search conducted through three main databases, namely PubMed, Cochrane, and Scopus, applying the inclusion and exclusion criteria set by the author, followed by a critical review. Result: There are four articles consisting of two systematic reviews/meta-analyses, one meta-analysis, and one randomized controlled trial (RCT) that meet the eligibility criteria. The validity of the study is assessed as quite good. The results from the four studies indicate that three meta-analyses did not show a significant effect on the improvement of HbA1c, while one RCT study demonstrated a significant effect on the improvement of HbA1c. Conclusion: Current findings do not provide convincing evidence to support folic acid supplementation as a therapeutic approach to reduce HbA1c in type 2 diabetes mellitus. The effect of folic acid supplementation on HbA1c in type 2 diabetes mellitus needs to be further investigated through ongoing randomized controlled clinical trials with a minimum duration of 12 weeks.